Exploring Paenibacillus terrae B6a as a sustainable biocontrol agent for Fusarium proliferatum - Smith, Enriquay; Daniel, Augustine Innalegwu; Smith, Chelsey; Fisher, Stacey; Nkomo, Mbukeni; Keyster, Marshall; Klein, Ashwil (Frontiers in Microbiology, 2025)
The reliance on chemical fungicides for crop protection has raised environmental and health concerns, prompting the need for sustainable and eco-friendly alternatives. Biological control, using antagonistic microorganisms like Paenibacillus terrae B6a, offers an eco-friendly approach to managing disease causing phytopathogens. The objective of the study was to assess the efficacy of P. terrae B6a as a biocontrol agent against Fusarium proliferatum PPRI 31301, focusing on its in vitro antagonistic activity, its impact on fungal morphology and enzymatic content, and its ability to mitigate pathogen-induced stress in maize plants. In vitro antagonistic activity of B6a against F. proliferatum was carried out using standard protocol. In planta assay was carried out by bio-priming of maize seeds with 1 × 106 CFU/mL of B6a and infected with F. proliferatum for 7 days. Biochemical, enzymatic and antioxidants activities of bio-primed maize roots under F. proliferatum infection was carried out using spectrophotometric methods. In vitro antagonistic assays using dual culture and intracellular crude metabolites inhibited 70.15 and 71.64%, respectively, of F. proliferatum. Furthermore, B6a altered the morphology and mycelia structure of F. proliferatum under High resolution scanning electron microscopy (HR-SEM). This was supported by an increase (p < 0.05) in the chitin contents (48.03%) and a decrease (p < 0.05) in the extracellular polysaccharide content (48.99%) and endo-β-1,4-glucanase activity (42.32%). The infection of maize seeds with F. proliferatum resulted in a significant decrease (p < 0.05) in root lengths (37%). Relative to the control and the infected seeds, bio-priming with B6a shows a significant increase (p < 0.05) in the root lengths (44.99%), with a significant decrease (p < 0.05) in reactive oxygen species (ROS)-induced oxidative damage. In conclusion, P. terrae B6a may be a good biocontrol candidate and may be formulated into a bio-fungicide to control F. proliferatum and other related phytopathogens in economically important crops.